ETNOMATEMATIKA PADA PROSES PENETASAN TELUR PENYU HIJAU SEMI ALAMI DI SUKAMADE, TAMAN NASIONAL MERU BETIRI SEBAGAI BAHAN AJAR SISWA BERBASIS FRAKTAL - Nila Lestari; Sunardi Sunardi; Erfan Yudianto; Toto Bara Setiawan; Dinawati Trapsilasiwi (Saintifika, 2019)
Abstract.Ethnomatematics is the practice or daily activities of a society that has become a culture and there is the application of basic mathematical concepts. The purpose of this research is to describe ethnomatematics on the activities of hatching process of semi-natural green turtle eggs in Sukamade, Meru Betiri National Park to make teaching materials for students in the form of test questions and calculate the fractal dimensions on sand used for hatching the eggs of green turtle. This type of research is qualitative research with an ethnographic approach. The data collection methods used are observation and interviews. The research subjects were the UPKP (Turtle Conservation Management Unit), MMP (Gamekeeper Partner Community) and Facilitators. This study focuses on the activities to calculate, measure, and design. The mathematical concepts that arise are arithmetic operations, value comparisons, arithmetic series and geometric shapes. Fractal dimension calculations on natural and semi-natural sand in the process of hatching green turtle eggs with MATLAB aid program obtained the fractal dimensions on natural sand was 1.7252 and on semi-natural sand was 1.7273. Keywords: Ethnomatematics, Green Turtle, Fractal Dimension